2017
DOI: 10.1158/1078-0432.ccr-17-0972
|View full text |Cite|
|
Sign up to set email alerts
|

Gene Copy Number Estimation from Targeted Next-Generation Sequencing of Prostate Cancer Biopsies: Analytic Validation and Clinical Qualification

Abstract: Purpose: Precise detection of copy number aberrations (CNA) from tumor biopsies is critically important to the treatment of metastatic prostate cancer. The use of targeted panel next-generation sequencing (NGS) is inexpensive, high throughput, and easily feasible, allowing single-nucleotide variant calls, but CNA estimation from this remains challenging.Experimental Design: We evaluated CNVkit for CNA identification from amplicon-based targeted NGS in a cohort of 110 fresh castration-resistant prostate cancer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 22 publications
0
24
1
Order By: Relevance
“…A recent study investigated the use of an amplicon-based sequencing strategy that targeted all exons of 113 genes related to DNA repair. 25 The researchers demonstrated that, with an appropriate analysis strategy and quality control, amplicon-based sequencing strategy is feasible and cost-effective for CNA profiling in FFPE samples. 25 In the present study, the strategy of computing and centering the log 2 ratios for the primer two pools separately, before merging and segmentation proved to be an effective strategy in resolving issues associated with variable amplification efficiencies, with 86% of the genes showing concordant copy number states.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study investigated the use of an amplicon-based sequencing strategy that targeted all exons of 113 genes related to DNA repair. 25 The researchers demonstrated that, with an appropriate analysis strategy and quality control, amplicon-based sequencing strategy is feasible and cost-effective for CNA profiling in FFPE samples. 25 In the present study, the strategy of computing and centering the log 2 ratios for the primer two pools separately, before merging and segmentation proved to be an effective strategy in resolving issues associated with variable amplification efficiencies, with 86% of the genes showing concordant copy number states.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 10 fresh-frozen pairs sequenced by using the HCC panel, one was excluded for excessive residual copy number log 2 ratio (segment interquartile range, >0.8). 25 For the nine evaluable samples, a correlation of r Z 0.80 (r 2 Z 0.64) was found between the copy number log 2 ratio of the two platforms ( Figure 5A). When the copy number profiles of the 34 evaluable FFPE tumors were compared with the matched profiles from WES, a correlation of r Z 0.73 (r 2 Z 0.54) was observed between the copy number log 2 ratios ( Figure 5A).…”
Section: Copy Number Analysis Of the Hcc Panel Reveals High Concordanmentioning
confidence: 92%
See 2 more Smart Citations
“…Libraries for next-generation targeted sequencing were constructed from 40 ng of DNA using a customized panel (Generead DNaseq Mix-n-Match Panel v2; Qiagen) as previously described (Mateo et al, 2015). CNVs were assessed from the aligned sequence files (.bam) using CNVkit v0.7.3 (Seed et al, 2017; Talevich et al, 2016; Turajlic et al, 2018).…”
Section: Methodsmentioning
confidence: 99%